Effect of sintering temperature on the electric properties of KNLNT ceramics. (3rd July 2020) - Zhang, Chunxiao; Wu, Fengmin; Wang, Junjun; Lin, Weipeng; He, Xunjun; Yang, Bin
Abstract: (K0.48 Na0.48 Li0.04 )(Nb0.8 Ta0.2 )O3 (KNN-LT) ceramics were prepared by the traditional solid-state reaction method. The combined effects of Li and Ta additions resulted in a decrease in the orthorhombic-tetragonal ( T O-T ) and Curie temperature ( T c ). The piezoelectric and electromechanical properties were found to be d 33 ∼ 165 pC/N, k t ∼ 0.438, k p ∼ 0.363 at the sintering temperature 1178 ˚C. It has a wide temperature range for ferroelectric properties and energy storage density and possess a good temperature stability.